The Impact of the E-Learning Module on Remediation of Misconceptions in Modern Physics Courses - A. Halim; Soewarno Soewarno; Elmi Elmi; Zainuddin Zainuddin; I. Huda; Irwandi Irwandi (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
The misconception in mastering physics concepts occurs in basic physics and is also found in advanced physics, such as Modern Physics or Quantum Physics. Efforts to remediate misconceptions have been done manually or offline but are often constrained at too long an interval between identification activities and remediation actions. Through the advancement of online learning systems, E-learning media, these obstacles can easily be overcome. This article will discuss one way of remediation using Moodle-based E-Learning modules. A total of 2 classes (45 students) were randomly selected for the experimental group and two classes (64 students) for the control group. The experimental group used a representative module based on E-Learning as a remediation treatment, while the control group used a conventional module. The results of the validation of the material and the design of the E-Learning modules were obtained as very feasible to use. Data collection uses a two-tier Modern Physic Diagnostic Test or MPDT (Modern Physic Diagnostic Test) of 30 items combined with the CRI (Certainty of Response Index) index. It is carried out twice, namely before and after treatment. The N-Gain normality analysis results showed the percentage of misconception reduction was more significant in the experimental group than in the control group. Important note obtained by implementing E-Learning is more appropriate to be used simultaneously between conventional face-to-face and E-Learning.